Efektivitas Pemberian Terapi Akupunktur Dengan Kombinasi Titik Akupunktur BL-23 (Shenshu), BL-40 (Weizhong) Dan BL-23 (Shenshu), KI 3 (Taixi) Terhadap Perbaikan Keluhan Nyeri Pada Kasus Nyeri Punggung Bawah Di Posyandu Lansia Klodran Dan Bendo Colomadu - Heni Nur Kusumawati; Estuningsih Estuningsih; Risna Widowati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Lower Back Pain (NPB) or Low Back Pain (LBP), VAS, Acupuncture Therapy, Healing Effect. Previous studies of acupuncture for low back pain were conducted. In this study, the researcher used a combination of BL 23. BL 40 and BL 23, KI 3. This study is aimed to determine the effectiveness of the combination of BL 23. BL 40 and BL 23, KI 3 for recovery low back pain. This study is done during March until May 2015 at Posyandu Lansia Klodran and Bendo Colomadu Karanganyar. This is a quasy experiment research with pre-test and post-test. Thirty subject studies were divided into two groups were treated combination of BL 23. BL 40 in the first group and BL 23, KI 3 in the second group. This treatment was conducted for 10 times. VAS was done before and after 10th therapy. The data obtained thus were analyzed using the Mann-Whitney test. Twenty-nine out of thirty subjects experienced decrease their VAS only one subject did not show any alteration. The average value of VAS decrease is 3.03. Acupuncture therapy with a combination of BL 23. BL 40 and BL 23, KI 3 has been shown that there are no differences between two groups (p>0.05)